Perceived Neighborhood Characteristics and Sleep in Australian Adults - Edmed, Shannon L.; Huda, M Mamun; Pattinson, Cassandra L.; Rossa, Kalina R.; Smith, Simon S. (My University, 2023)
Background: Poor sleep can contribute to poorer health and socioemotional outcomes. Sleep health can be influenced by a range of individual and other socioecological factors. Perceptions of neighborhood physical and social characteristics reflect broader social-level factors that may influence sleep, which have not been well studied in the Australian context. This study examined the association between perceived neighborhood characteristics and sleep in a large sample of Australians. Methods: Data were from 9,792 people aged 16 years or older, from Waves 16 and 17 of the nationally representative Household, Income and Labour Dynamics in Australia Survey. Associations between perceived neighborhood characteristics (neighborly interaction and support, environmental noise, physical condition, and insecurity) and self-reported sleep duration, sleep disturbance, and napping were examined using multiple logistic regression models. Results: “Neighborhood interaction and support” and “neighborhood physical condition” were not significantly associated with any sleep outcomes after adjusting for relevant covariates. However, “environmental noise” and “neighborhood insecurity” remained significantly associated with sleep duration and sleep disturbance. None of the neighborhood characteristics were associated with napping. Furthermore, associations did not significantly vary by gender. Conclusions: This study highlights the potential benefit of public health policies to address noise and safety in neighborhoods to improve sleep.
Health Education & Behavior
Keywords: Disadvantage, adversity and resilience; Health and wellbeing; Housing, communities and neighbourhoods